The Politics Of Agrarian Conflict And Community Struggles For Land Access Rights: The Role Of Contemporary Education - Ricco Andreas; Suci Flambonita; Raesitha Zildjianda (Fakultas Hukum Universitas Lampung, 2025)
The agrarian conflict in Moro-Moro Register 45, Mesuji Regency, Lampung, has significantly impacted the local community, particularly in restricting children's access to education. The enforcement of Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction and Law No. 30 of 2014 on Government Administration has further complicated the situation by limiting the community's rights to manage and utilize natural resources, making it difficult for residents in forest areas to access adequate educational services. This research examines two key issues: the role of education as a tool of resistance for the Moro-Moro Register 45 community in defending their rights and the impact of agrarian conflict on their struggle for land access. Using a qualitative and socio-legal approach, this research integrates legal analysis with social inquiry, drawing on desk research, direct observations, and in-depth interviews with community members and stakeholders. The findings indicate that the politics of education is a crucial instrument for the Moro-Moro community in advocating for social change, particularly in addressing agrarian disputes and seeking social justice at the governmental level. Furthermore, agrarian conflicts often stem from systemic injustices in the distribution and management of natural resources, with land emerging as a central point of contention between the state, private enterprises, and local communities or small-scale farmers.